2011
DOI: 10.1530/eje-10-0877
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk, metabolic profile, and body composition in adult males with congenital adrenal hyperplasia due to 21-hydroxylase deficiency

Abstract: Objective: Lifelong glucocorticoid therapy in patients with congenital adrenal hyperplasia (CAH) or the disease per se may result in increased cardiovascular risk. We therefore investigated cardiovascular and metabolic risk profiles in adult CAH males. Subjects and methods: We compared CAH males (nZ30), 19-67 years old, with age-and sex-matched controls (nZ32). Subgroups of different ages (!30 years or older) and CYP21A2 genotypes (null, I2splice, and I172N as the mildest mutation) were studied. Anthropometry,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
111
1
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(120 citation statements)
references
References 38 publications
3
111
1
5
Order By: Relevance
“…Although we did not find higher BMI than the reference population, we found markedly increased body fat mass in both men and women. The high fat mass in younger women is at variance with data from Sweden showing fat mass in female and male 21OHD patients similar to age-matched controls but increased fat mass in male patients older than 30 years (32,33). One explanation could be the higher hydrocortisone equivalent dose used by the young Norwegian females (38.9 mg/day) compared with the young Swedish females (33.3 mg/day).…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Although we did not find higher BMI than the reference population, we found markedly increased body fat mass in both men and women. The high fat mass in younger women is at variance with data from Sweden showing fat mass in female and male 21OHD patients similar to age-matched controls but increased fat mass in male patients older than 30 years (32,33). One explanation could be the higher hydrocortisone equivalent dose used by the young Norwegian females (38.9 mg/day) compared with the young Swedish females (33.3 mg/day).…”
Section: Discussionmentioning
confidence: 57%
“…The glucocorticoid doses were also higher than the hydrocortisone doses of 15-25 mg/day suggested by the Endocrine Society (3). We previously reported that only 47% of the Norwegian patients use mineralocorticoid (17), which compared with 84% of the Swedish patients (32,33), which could contribute to the differences in both glucocorticoid doses and body composition. High blood pressure, including isolated diastolic hypertension, is, like fat mass, a marker of risk of cardiovascular disease (34).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Male controls, one for each patient and born on the same date as each patient, were recruited from the National Population Registry. Characteristics of this cohort have been reported earlier (25,26).…”
Section: Subjectsmentioning
confidence: 99%
“…Testosterone, estradiol and dried blood spot 17OHP (measured at 0800, 1400, 1900, 0100, and 0600 h), and 24-h urinary pregnanetriol were measured as described previously (25,26 …”
Section: Biochemical Assaysmentioning
confidence: 99%